The Relationship Between Water Physical Quality and Skin Disease Complaints in KB Village, Percut Sei Tuan District - Syahputri, Nuri Nabila; Nanda, Meutia; Syahrani, Putri; Aisyah, Siti Nur; Kholijah, Anna (PROMOTOR, 2024)
Clean water is a basic need for humans, so its availability is very important. Clean water quality can have an impact on health. However, if the quality of clean water does not meet the requirements, such as a fishy odor and a yellow-brown water color, then this can result in skin diseases. This research aims to determine the condition of the physical quality of water used by the community and determine the relationship between the physical quality of water and complaints of skin diseases. Quantitative research using the chi-square analysis test was used on a population of 680 families and a sample of 55 respondents were obtained which were randomly selected. The results of this study show that the relationship between physical water quality and complaints of skin diseases obtained a significance value of 0.011 < 0.05. The conclusion of this research is that the physical quality of water influences complaints of skin diseases in KB village, Percut Sei Tuan District. Researchers submit suggestions to the Government to provide more physical water facilities to the people of Kampung KB and the community is expected to pay attention to the physical quality of water to avoid complaints of skin diseases.